Exercise and lactational performance : the role of exercise intensity and the timing of an acute exercise bout - Jander, Caron Bridget (Not Specified, 2024)
The purpose of this study was to determine whether an acute exercise bout in lactating women performed at two different exercise intensities and at different time intervals between exercise and feeding, affects breast milk composition, production and lactate concentration. Eight untrained women, whose infants were 6-12 weeks old and exclusively breast-fed, participated in the study. In the first experiment, breast milk volume, macronutrient composition and lactate concentration were measured after cycle ergometer exercise at 50 % or 70 % of peak power output (PPO). In the second experiment, these same parameters were compared after cycle ergometer exercise performed at 70% PPO immediately before a feed, 90 minutes before a feed or 180 minutes before a feed. Milk was manually expressed by the investigator from the alternate breast while mothers fed their infants. Milk samples were frozen and stored for later analysis. Infants were test weighed before and after each feed. Each subject acted as her own control. The results indicated that an acute exercise bout of moderate intensity (50 - 70 % of PPO) did not significantly alter breast milk volume, nutrient and energy composition. There was, however a significant increase in breast milk lactate concentration at 70 % PPO (p< 0,05). There was also no effect of the timing of an acute exercise bout in relation to the infant's feed on breast milk volume, nutrient and energy composition. Furthermore, no alterations in infant feeding patterns were observed when the mothers exercised at X different intensities and at different time intervals between the exercise bout and feeding. In conclusion, there are no apparent adverse effects of an acute exercise bout of moderate intensity(< 70% of PPO) in untrained women on breast milk volume, composition and energy content.